Effect of Sulfate or Hydroxychloride Forms of Zinc, Manganese, and Copper on Growth Performance, Weight Variation, Carcass Characteristics, and Economics of Grow-Finish Pigs - Hilario M. Cordoba; Jason C. Woodworth; Robert D. Goodband; Joel M. DeRouchey; Mike D. Tokach; Jordan T. Gebhardt; Chris P.A. van de Ligt (Kansas Agricultural Experiment Station Research Reports, 2023)
A total of 1,026 grow-finish pigs (337 × 1050 PIC; initially 57.2 ± 0.73 lb) were used in a 124-d trial to compare sulfate and hydroxychloride forms of Zn, Mn, and Cu on growth performance, carcass characteristics, weight variation, and economics of grow-finish pigs. Pigs were housed in mixed gender pens with 27 pigs per pen and 19 pens per treatment. The treatments were structured as a completely randomized design and consisted of a control diet containing 150, 16, and 110 ppm of Cu, Mn, and Zn, respectively, from sulfate sources or the same inclusion provided by hydroxychloride sources. Experimental diets were corn-soybean meal-DDGS-based and fed in meal form in phase 1 from 57 to 110 lb, phase 2 from 110 to 165 lb, phase 3 from 165 to 220 lb, and phase 4 from 220 to 300 lb. In the grower period (57 to 173 lb), there was a tendency (P= 0.052) to improve F/G when sulfate Mn, Zn, and Cu were fed. In the finisher period (d 61 to 124), pigs fed hydroxychloride mineral sources had improved (P= 0.041) ADG. For pig body weight variability, there was no evidence of differences (P≥ 0.10) on the coefficient of variation between treatments. Pigs marketed at the end of the study which were fed hydroxychloride sources tended to have greater HCW (P= 0.054) compared to sulfate sources, but no evidence for differences (P≥ 0.10) were found in any other carcass trait at any marketing event. There was a tendency (P= 0.088) to reduce feed cost per lb of gain when using sulfate sources compared to hydroxychloride forms; however, IOFC was not impacted by mineral source (P>0.10). In conclusion, these data suggest there were no differences in pig weight variability, overall pig growth performance, or carcass characteristics between mineral sources.
Keywords: carcass characteristics; finishing pigs; hydroxychloride minerals; growth performance